PERSONAL BRANDING CONSTRUCTION ON GEN Z INSTAGRAM: DIFFERENCES IN SELF-PRESENTATION ON GEN Z'S FIRST AND SECOND ACCOUNTS - Ruslan, Salwa Azzahra; Wiryany, Detya; Tawaqal, Rizki Surya (Journal of Digital Media Communication, 2025)
This study examines the construction of personal branding on Instagram among Gen Z by comparing self-presentation on primary and secondary accounts. Using Erving Goffman's (1959) dramaturgy theory as the main framework, this study highlights how Gen Z conducts impression management through digital media, where Instagram functions as a "stage" where they present various versions of themselves. Core concepts used include impression management, front-stage–back-stage dynamics, and self-disclosure. This study does not establish formal hypotheses, but tentatively expects differences in self-presentation strategies between the two types of accounts. The method used is a descriptive qualitative approach. Data were collected through in-depth interviews with selected informants using a purposive sampling technique based on certain criteria: Gen Z individuals aged 18–22 who actively use both types of Instagram accounts. The main focus of this study was to observe patterns of self-expression and image management on each account. To ensure the validity of the data, source triangulation techniques were used. The results show that primary accounts are used as a front stage to display a curated and socially accepted self-image, such as achievements or aesthetic content. In contrast, the second account serves as a more authentic, expressive, and emotional backstage, aimed at a closer social circle. This finding supports Goffman's theory and aligns with previous research. In conclusion, Instagram allows Gen Z to strategically construct and display multiple identities. This study contributes to communication studies by demonstrating the role of social media in shaping personal branding in the digital age.